Improving Students’ Speaking Skill through the Picture and Picture Cooperative Learning Model - Edwin Tang Yiu; Patrick Chou (JELITA, 2021)
The present research is conducted in an elementary school in Tan Shan city, Hong Kong, at the academic year of 2020-2021, on 40 students consisting of 16 boys and 24 girls. The research result shows that the application of the picture and picture cooperative learning model can improve the speaking skill of elementary school students. This is indicated by the increasing of students’ speaking skill score. In the first cycle, the average score was 62.2, students who did not complete were 62.5%, and those who completed 37.5% (in the low category). In cycle II, the average score was 80.8, 12.5% ​​were incomplete and 87.5% were completed. This proves an increase. Likewise, students’ attendance, students’ activity in listening to the teacher’s explanation, students’ activity in asking questions to the teacher, students’ activity in answering teacher questions, students’ activity in commenting on the content of the picture, and students’ activity in concluding subject matter, increased in the cycle II. Based on the results of the analysis above, the conclusion is that students’ speaking skill increases through the application of the picture and picture cooperative learning model.